2021
DOI: 10.7189/jogh.11.04027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and viral etiology of community-acquired acute lower respiratory tract infection among older adults in rural north India

Abstract: Background There are limited data on incidence, risk factors and etiology of acute lower respiratory tract infection (LRTI) among older adults in low- and middle-income countries. Methods We established a cohort of community dwelling older adults ≥60 years and conducted weekly follow-up for acute respiratory infections (ARI) during 2015-2017. Nurses assessed ARI cases for LRTI, collecting combined nasal/throat swabs from all LRTI cases and an equal number of age- and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This hypothesis assumes that older adults in decompensation are infected with RSV. This has been confirmed in the recent literature, which clearly shows that this virus is found in these clinical situations [33,34] and that it is responsible for a non-negligible fraction of cases [35] on the one hand. On the other hand, this hypothesis implies that RSV circulates in an epidemic mode and that its circulation, when it exists, is massive.…”
Section: Implications For Clinicians or Managerssupporting
confidence: 74%
“…This hypothesis assumes that older adults in decompensation are infected with RSV. This has been confirmed in the recent literature, which clearly shows that this virus is found in these clinical situations [33,34] and that it is responsible for a non-negligible fraction of cases [35] on the one hand. On the other hand, this hypothesis implies that RSV circulates in an epidemic mode and that its circulation, when it exists, is massive.…”
Section: Implications For Clinicians or Managerssupporting
confidence: 74%
“…In 2016, an estimated 2.38 million LRTI‐associated deaths occurred across all age groups worldwide 1 . Influenza and respiratory syncytial virus (RSV) are among the most common causes of LRTIs during typical (i.e., non‐pandemic) endemic seasons, 2 with influenza causing an estimated 1 billion infections 3 and RSV causing an estimated 64 million acute respiratory infections 4 globally each year. A systematic analysis from the Global Burden of Diseases, Risk Factors, and Injuries study found that influenza caused ~500,000 deaths and RSV caused 250,000 deaths annually worldwide 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Among SARI cases, influenza virus was detected in 27% of pregnant women, 12.4% of cases with pre-existing chronic diseases and 12.7% adults �60 years. Studies from India during the same period had shown high incidence of influenza in pregnant women (68 to 90 per 10,000 pregnant women months) and older adults (influenza associated lower respiratory infection incidence:7.9 per 1000 person years) [19,20]. High burden of influenza among these WHO Strategic Advisory Group of Experts (SAGE) target groups suggests that value proposition of influenza vaccination and early interventions (early detection and antiviral treatment) among these groups need to be explored by the country.…”
Section: Discussionmentioning
confidence: 99%